THE FEASIBILITY ANALYSIS OF BOEING 737-500 OPERATION AT NORTH ACEH MALIKUSSALEH AIRPORT - R, Aldrian Nasaifal (Vortex, 2021)
The large number of Acehnese people who are outside Aceh with various needs, such as doing business, working or studying. The optimal transportation to use to the destination quickly in a short time, namely air transportation. North Aceh Malikussaleh Airport is the second busiest airport in Aceh Province.The analysis in this study used PKP-PK analysis, analysis of the feasibility of Boeing 737-500 aircraft using the FPPM method, and analysis of the load capacity of Boeing 737-500 aircraft.From the calculation results, the Boeing 737-500 aircraft is not suitable to be flown at the Malikussaleh Airport in North Aceh due to the limitations of the PKP-PK category level and the strength of the Malikussleh Airport runway. Therefore, North Aceh Malikussaleh Airport must be upgraded